2017
DOI: 10.1021/acsnano.7b03116
|View full text |Cite
|
Sign up to set email alerts
|

Design of Oxygen Vacancy Configuration for Memristive Systems

Abstract: Oxide-based valence-change memristors are promising nonvolatile memories for future electronics that operate on valence-change reactions to modulate their electrical resistance. The memristance is associated with the movement of oxygen ionic carriers through oxygen vacancies at high electric field strength via structural defect modifications that are still poorly understood. This study employs a CeGdO solid solution model to probe the role of oxygen vacancies either set as "free" or as "immobile and clustered"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 72 publications
3
100
0
Order By: Relevance
“…The method was previously successfully applied in measuring oxygen vacancy mobilities in reduced molybdenum trioxide thin films at near ambient temperatures . Here, we use the dynamic I–V analysis to measure oxygen vacancy mobilities in ten percent praseodymium‐doped ceria, Pr 0.1 Ce 0.9 O 2− δ (PCO), MIEC thin films of interest as a cathode model material in SOFCs at elevated temperatures and for room temperatures nanoelectronic applications . Models for oxygen vacancy formation and transport in PCO are reviewed in Appendix .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method was previously successfully applied in measuring oxygen vacancy mobilities in reduced molybdenum trioxide thin films at near ambient temperatures . Here, we use the dynamic I–V analysis to measure oxygen vacancy mobilities in ten percent praseodymium‐doped ceria, Pr 0.1 Ce 0.9 O 2− δ (PCO), MIEC thin films of interest as a cathode model material in SOFCs at elevated temperatures and for room temperatures nanoelectronic applications . Models for oxygen vacancy formation and transport in PCO are reviewed in Appendix .…”
Section: Introductionmentioning
confidence: 99%
“…This is technologically relevant as it shows that extrapolation of MIEC ionic transport coefficients to low temperatures applicable to, e.g., memristive devices operated at room temperature, utilizing out‐of‐equilibrium quenched MIEC materials, is justified. We demonstrated that the dynamic I–V analysis can be applied to crossbar devices, the same configuration used for implementation and study of memristive devices …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest two categories of memristive devices—valence change memories and electrochemical metallization memories—rely on creation, annihilation, and motion of ions and defects through ionic conductors under a bias (which is used to control resistive state). Valence change memories are based on transition metal oxides whose resistive state depends on the redistribution of bulk O 2– and O 2– vacancies under bias (and resulting reduced metal cations) . Typical diffusivity values for state‐of‐the‐art switching oxides (SrTiO 3 , TiO 2 and TaO x ) are 10 −15 –10 −13 cm 2 s −1 at ambient temperature.…”
mentioning
confidence: 99%
“…Interestingly, as a widely‐recognized rare earth oxide, cerium oxide (CeO 2 ) has a unique oxygen storage and release capacity, prominent reversible redox property (Ce 3+ /Ce 4+ ) and possesses a large number of oxygen vacancies, which are beneficial to ORR catalytic processes . Especially, CeO 2 is possible to stabilize more nitrogen sources during catalyst synthesis process .…”
Section: Introductionmentioning
confidence: 99%